Annual Plan 1998-99 Government of Himachal Pradesh - Planning Commission (Planning Commission, 1998)
On 1st September 1972, two more districts viz. Hamirpur and Una were created by trifurcation of Kangra district and the Mahasu and Solan districts were reorganised as Shimla and Solan districts. In this re-organisation, Shimla town was re-organised with the erstwhile Mahasu district to form Shimla district.
Planning Department, Government of Himachal Pradesh